2014
DOI: 10.1093/ptep/ptu138
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics on non-commutative space: A step toward hydrodynamics of granular materials

Abstract: Hydrodynamics on non-commutative space is studied based on a formulation of hydrodynamics by Y. Nambu in terms of Poisson and Nambu brackets. Replacing these brackets by Moyal brackets with a parameter θ, a new hydrodynamics on non-commutative space is derived. It may be a step toward to find the hydrodynamics of granular materials whose minimum volume is given by θ. To clarify this minimum volume, path integral quantization and uncertainty relation of Nambu dynamics are examined.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The same observation has been made by Yoichiro Nambu in the description of an incompressible liquid (private communication, see also[36][37][38]. )…”
supporting
confidence: 69%
“…The same observation has been made by Yoichiro Nambu in the description of an incompressible liquid (private communication, see also[36][37][38]. )…”
supporting
confidence: 69%
“…Now we introduce the non-commutativity in space coordinates, and find the additional terms which will appear. This was carried out in [3] where the noncommutativity is introduced by replacing the Nambu-Poisson brackets with the Moyal brackets [4]. We discuss the two dimensional hydrodynamics in this paper, so the Moyal bracket becomes…”
Section: Hydrodynamics On Non-commutative Spacementioning
confidence: 99%
“…Now, the Navier-Stokes equation of the hydrodynamics on the 2 dimensional non-commutative space is given by [3] ρ Dv Dt + ∇p − η∆v = K (13)…”
Section: Hydrodynamics On Non-commutative Spacementioning
confidence: 99%
“…In order for the Liouville theorem to hold in the N -dimensional extended phase space, the Nambu equations are defined by N − 1 Nambu Hamiltonians and the Nambu bracket, an N -ary generalization of the Poisson bracket. The structure of Nambu mechanics has impressed many authors, who have reported studies on its fundamental properties and possible applications, including quantization of the Nambu bracket [2][3][4][5][6][7][8][9][10][11]. However, the applications to date have been limited to particular systems, because Nambu systems generally require multiple conserved quantities as Hamiltonians and the Nambu bracket exhibits serious difficulties in systems with many degrees of freedom or quantization [1,2,10].…”
Section: Introductionmentioning
confidence: 99%